Analysis of Murabahah Financing Risk Management Strategies at PT. BPRS Al-Washliyah Medan - Gemilang, Fajar; Hutagalung, Muhammad Abrar Kasmin (Fakultas Ekonomi dan Bisnis, Universitas Hasyim Asy'ari Tebuireng Jombang, 2025)
This study analyzes risk management strategies in murabahah financing at PT. BPRS Al-Washliyah Medan. Murabahah dominates approximately 95% of the bank's total financing portfolio, creating potential non-performing financing (NPF) risks. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation with management and staff. Data analysis in this study used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that the main risks include credit, liquidity, operational, and market risks. The causes of financing problems arise from internal factors such as weak financing analysis and external factors such as customer inability to pay and economic fluctuations. To mitigate these risks, PT. BPRS Al-Washliyah Medan applies the 5C principle of character, capacity, capital, collateral, and economic conditions—and the 3R strategy of rescheduling, reconditioning, and restructuring. The implementation of these steps effectively minimizes the NPF level and improves the bank's financial stability. Overall, this study emphasizes the importance of robust risk management practices to maintain business performance and maintain customer trust in Islamic banking. The findings also provide valuable insights for improving risk management in Islamic financial institutions and serve as a reference for further research on murabahah financing risks.